Kualitas Produk, Kesadaran Merek dan Harga serta Pengaruhnya Terhadap Kepuasan Pelanggan - Didit Darmawan (Jurnal Administrasi Bisnis, 2019)
The growing of restaurant industry is causing high competition among business competitor, each business is required to create competitive advantage to satisfy customers and increase the level of sales. Business people in this industry strive to achieve maximum satisfaction for their customers and not only to achieve profits. This is because satisfied customers will determine the sustainability of the relationship with the restaurant. Every effort should be made to get satisfied customers with restaurant services. This study aims to analyze and discuss the influence of product quality, brand awareness and price on customer satisfaction in Dewi Kahyangan restaurant in Jombang City. The three independent variables involved in this study are product quality, brand awareness and price. One dependent variable is customer satisfaction. The research method used was qualitative. The sampling technique used wasnon-probability sampling. The population in this research all custumes who had eaten at the Dewi Kahyangan restaurant in Jombang City, with 100 respondents of sample size.The technique for taking samples is used non probability sampling techniques with accidental sampling method. The analytical tool used was multiple linearregression with SPSS 24.0 for windows. The results showed that product quality, brand awareness and price had a significant partial and simultaneous effect on customer satisfaction.